Mortality predictors six months after discharge from an Acute Geriatric Unit, 2016 - Tuesta-Nole, Juan Rodrigo (2017)
Objective: To determine the variables of the comprehensive geriatric assessment (CGA), predictors of mortality six months after discharge of inpatients from the Acute Geriatric Unit (AGU) of the Hospital Nacional Guillermo Almenara Irigoyen. Materials and methods: An observational, prospective, longitudinal study was conducted in the Acute Geriatric Unit of the Hospital Nacional Guillermo Almenara Irigoyen (HNGAI) from July 2015 to January 2016. Variables (general characteristics [age, gender, hospital stay] and comprehensive geriatric assessment [comorbidity, functional assessment, emotional assessment, cognitive assessment and social-family assessment]) were collected from the Geriatric Unit medical records and a mortality-related telephone follow-up was performed six months after discharge. Results: The study population consisted of 110 patients (57.3% were male, age: 77.47 ± 8.92 years, hospital stay: 29.29 ± 44.03 days). Six months after discharge, mortality was 42%. The bivariate analysis showed that variables associated with mortality six months after discharge were greater loss of functional capacity at admission, comorbidity, functional dependence, greater cognitive impairment, and risks and social problems. Cox regression analysis showed that predictors of mortality were loss of functional capacity at admission (PFi) (HR [95% CI] = 1.09 [1.03-1.15]; p = 0.005) and comorbidity (Charlson Index) (HR [95% CI] = 5.74 [0.817-37.75]; p = 0.05). Conclusions: Greater loss of functional capacity and comorbidity were variables of the comprehensive geriatric assessment, predictors of mortality six months after discharge, which allow identifying the risk group, in order to establish intervention strategies to improve the continuity of care process and increase the follow-up time of frail elderly.